METODE TALKING STICK TERHADAP KEMAMPUAN BERBICARA ANAK AUTIS DI SEKOLAH LUAR BIASA - AYU LIBRAYANTI, NINDYA; MAHMUDAH, SITI (Jurnal Pendidikan Khusus, 2018)
This study is based on the obstacles in the ability to speak to children with autism. Based on these obstacles then conducted research on the influence of talking stick method to the ability to speak autistic children in SLB Harmoni Sidoarjo. The purpose of this study was to determine the effect of talking stick method on the ability to speak autistic children in SLB Harmoni Sidoarjo.The research approach used is quantitative approach with pre experper experimental desigh and one group pre test-post test design. The statistical technique used in data analysis is the wilcoxon matched pairs test. Technique of collecting data in the form of test and observation. The results showed that T = 0 is equal to the critical value of T? (table) 5% (two-sided test) ie 2 means T ? T?, which can be interpreted that there is influence between talking stick method to the ability of speaking autistic children in SLB Harmoni Sidoarjo. Keywords: talking stick method, talking, autism